Reflections on wage-setting - Klaus F. Zimmermann (Global Labor Organization (GLO), 2018)
Central banks need to be concerned about wages since they are a major driver of inflation. Rising wages are needed to signal directions for market adjustments to ensure growth. Wage growth is driven by relative scarcity, labor productivity and expectations about inflation and future growth. Migration plays a significant role to balance wages across regions and countries. Wage growth has been low in most developed economies because of underutilized labor if properly measured. Germany seems to be an exception, but the scarcity of workers has been tamed by internal flexibility resulting from more decentralized wage setting and labor market reforms.
Keywords: E24; J31; J52; J61; 330; Phillips-curve; wages; union wages; decentralized wage bargaining; labor market reforms; internal flexibility; unemployment; underemployment; mobility and wages